2019
DOI: 10.11591/ijeecs.v14.i1.pp413-420
|View full text |Cite
|
Sign up to set email alerts
|

Emotional augmented reality-based mobile learning design elements: a kansei engineering approach

Abstract: <span>In recent times, various studies have shown that Augmented Reality (AR) will be the next wave of online learning. This is because of the advent of powerful smartphones that has changed user experiences, thereby able to increase the capability of AR. There has been much concentration in previous studies on cognition towards the use of AR in education, in which little consideration has been given to emotions which is also an important aspect in learning. Based on this, the present research aims to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The cloud governance can be initiated by creating guideline and policy, negotiating and having clear SLA, investigating about legal and act, data geographical and level of data privacy impact. There are growing research on blended learning, online learning and mobile learning [23][24][25][26][27][28][29]. The Malaysia Education Blueprint 2015-2025 roadmap towards higher income nation by producing holistic, excellent graduates and lifelong learners through independent and democratize access towards learning when higher education institutions adopted cloud computing services as the universities' IT service platform.…”
Section: Resultsmentioning
confidence: 99%
“…The cloud governance can be initiated by creating guideline and policy, negotiating and having clear SLA, investigating about legal and act, data geographical and level of data privacy impact. There are growing research on blended learning, online learning and mobile learning [23][24][25][26][27][28][29]. The Malaysia Education Blueprint 2015-2025 roadmap towards higher income nation by producing holistic, excellent graduates and lifelong learners through independent and democratize access towards learning when higher education institutions adopted cloud computing services as the universities' IT service platform.…”
Section: Resultsmentioning
confidence: 99%
“…Nine [12], [6], [46], [47], [48], [49], [50], [51] and [52] of the 50 studies indicated that there were challenges that related to a need for identifying and using instructional design guidelines to design mobile training content. Seventeen studies [6], [53], [54], [55], [44], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], and [67] mentioned challenges related to adapting and appropriating mobile learning technology to learn in a compatible way with suitable learning theories, objectives and actual training/learning needs.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are taken into consideration in generating the EEG dataset for emotion recognition, including [11]: a) Stimulus media: The literature studies showed several categories of stimuli to evoke emotions such as audio [16], [17], visual, and audio-visual media [14] as well as others including the ambient assisted living (AAL) technology [18], a combination of music, video, and game stimuli [19], mobile learning application [20], augmented reality (AR) [21], virtual reality (VR) [22], [23], and tactile enhanced multimedia (TEM) [24]. b) Proper stimuli presentation setup [11].…”
Section: Rq 1: What Factors Need To Be Considered To Generate and Distribute Eeg Data To Represent Emotional Reactions?mentioning
confidence: 99%